Chapter Adalberto Alves e l'aforisma - Graziani, Michela (Studi di Traduzione Letteraria Lusofona, 2020)
The aphorism is the literary form choosen by the Portuguese poet Adalberto Alves in the collection A presença dos dias / La presenza dei giorni. The essay aims to analyse the concept of aphorism in Adalberto Alves with an eastern and western philosophical view.